2003
DOI: 10.1103/physrevc.68.034909
|View full text |Cite
|
Sign up to set email alerts
|

Chromodynamic Weibel instabilities in relativistic nuclear collisions

Abstract: Employing a previously derived formulation, and extending the treatment from purely transverse modes to wave vectors having a longitudinal component, we discuss the prospects for the occurrence of Weibel-type color-current filamentation in high-energy nuclear collisions. Numerical solutions of the dispersion equation for a number of scenarios relevant to RHIC and LHC suggest that modes with (predominantly transverse) wave numbers of several hundred MeV may become moderately agitated during the early collision … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
114
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 17 publications
(21 reference statements)
2
114
0
Order By: Relevance
“…In recent years the study of anisotropic plasma has received much interest due to the fact that the QGP, which has a local momentum-space anisotropy, is subject to the chromo-Weibel instability [64,66,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. The effects of these instabilities are not very clear, but they are very important for the QGP evolution at the RHIC or LHC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years the study of anisotropic plasma has received much interest due to the fact that the QGP, which has a local momentum-space anisotropy, is subject to the chromo-Weibel instability [64,66,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86]. The effects of these instabilities are not very clear, but they are very important for the QGP evolution at the RHIC or LHC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent calculations assuming a hadronizing QGP out of chemical equilibrium with subsequent hadronic rescatting have shown that rescatting via binary collisions in the hadronic phase is insufficient to drive the system toward chemical equilibrium before the expansion of the system leads to chemical freeze-out [21]. Currently the most favored approaches for explaining the rapid thermalization of the medium are either centered around turbulent color fields [22,23,24,25,26] or multi-particle collisions (which may take place either in the deconfined or dense, confined phase of the reaction) [27,28,29,30]. A smoking gun signature for either mechanism remains yet to be established.…”
Section: Hadron Yields and Ratiosmentioning
confidence: 99%
“…This instability has in fact close connections with the Weibel instabilities encountered in the physics of anisotropic plasmas [12][13][14], and it is speculated that such an instability may help the system created after heavy ion collisions reach a state of local equilibrium [15][16][17][18][19][20][21]. Whether or not such instabilities can grow to sufficient magnitude as to become as large as the classical solution is the subject of current investigations.…”
Section: Introductionmentioning
confidence: 99%